Perlindungan Hukum Terhadap Keterlambatan Pembayaran Spaylater Pengguna Shopee dalam Perspektif Hukum di Indonesia - Sisda Adisti Faizun; Rumawi Rumawi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Spaylater is a payment method that provides loans to its users. When carrying out transactions on Shopee e-commerce, legal protection is very necessary when there is a problem with late payments by users, viewed from the perspective of consumer protection law and civil law. The focus of this research is: 1) What is the Shopee application spaylater agreement system according to consumer protection law and civil law. 2) What is the impact of delays in Sypalater payments for Shopee users and Spaylater owners according to consumer protection law and civil law? 3) What is the legal protection against delays in spaylater payments for Shopee users according to consumer protection law and civil law. This research uses a sociological approach to law and legislation, with an empirical research type. The research results and conclusions are: 1) the Spaylater agreement system has aspects that require more attention from the perspective of consumer protection law and civil law. Although in general this agreement is valid according to civil law, there are still several inconsistencies with the principles regulated in the UUPK. 2) SPayLater payment delays can have a bad impact on Spaylater users. For loan service providers, late payments can be considered a breach of contract on the loan agreement. However, the application of sanctions or fines must still take into account the principles of consumer protection and must not burden consumers unreasonably. A balance is needed between protecting consumer rights and the interests of loan service providers in the context of late SPayLater payments. 3) Legal protection for Spaylater users who experience delays in payment must pay attention to the provisions in the Consumer Protection Law and Civil Law. In the UUPK, SPayLater service providers are required to provide clear and transparent information, and treat users fairly without discrimination. Meanwhile, in Civil Law, although late payment can be considered a breach of contract, the imposition of sanctions must still take into account the principles of propriety and good fait